Supersizing the mind embodiment, action, and cognitive extension - Clark, Andy, 1957- (Oxford : Oxford University Press, 2008)
This is a comprehensive tour of work in embodied and situated cognition. It describes and defends one clear option among a large and unruly space of alternatives.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Philosophy of mind; Mind and body; Distributed cognition